Neutralized ion beam modification of cellulose membranes for study of ion charge effect on ion-beam-induced DNA transfer - K. Prakrajang (2018)
Low-energy ion beam biotechnology (IBBT) has recently been rapidly developed worldwide. Ion-beam-induced DNA transfer is one of the important applications of IBBT. However, mechanisms involved in this application are not yet well understood. In this study plasma-neutralized ion beam was applied to investigate ion charge effect on induction of DNA transfer. Argon ion beam at 7.5 keV was neutralized by RF-driven plasma in the beam path and then bombarded cellulose membranes which were used as the mimetic plant cell envelope. Electrical properties such as impedance and capacitance of the membranes were measured after the bombardment. An in vitro experiment on plasmid DNA transfer through the cellulose membrane was followed up. The results showed that the ion charge input played an important role in the impedance and capacitance changes which would affect DNA transfer. Generally speaking, neutral particle beam bombardment of biologic cells was more effective in inducing DNA transfer than charged ion beam bombardment. © 2011 Elsevier B.V. All rights reserved.